Big head, big trouble? can a large fetal head circumference predict complicated delivery?. (18th April 2012) - Donnelly, JC; Cooley, SM; Burke, N; Walsh, J; Geary, M; Breathnach, F; Burke, G; Daly, S; Higgins, JR; Dornan, J; Morrison, JJ; McAuliffe, F; et al.
Abstract : This study evaluated the predictive value of fetal head circumference (FHC) for difficult birth and assessed the correlation between FHC and neonatal head circumference (NHC). A prospectively collated database was analysed for maternal age, body mass index (BMI), fetal biometry, labour and neonatal outcomes. Delivery was considered complicated if achieved by emergency Caesarean section (EmCS) or operative vaginal delivery, while spontaneous vertex delivery was classified as 'uncomplicated'. Delivery by elective CS was excluded. Data analysis was performed using SAS software. 583 nulliparous singleton term pregnancies were included for analysis. FHC was measured at a mean gestational age of 35.4 weeks. 43% (252) had an uncomplicated delivery. 57% (333) had a complicated delivery (EmCS =24.8% (145), forceps = 4.5% (26), vacuum = 25.9% (151), vacuum plus forceps = 1.5% (9)). A FHC of 34cm at 35 weeks' gestational age was identified as the 90th centile. Sonographic measurement of FHC consistently underestimated NHC by 3.0cm (8.5%). Odds ratio (OR) for having a "difficult birth" if the FHC was greater than the 90% centile was 2.8 (95% CI 1.3-6.3). The OR increases further with increasing age (OR=1.5, 95% CI 1.3-1.8) and increasing BMI (OR 1.2, 95% CI 1.0-1.6). Despite underestimating NHC by an average of 8%, FHC greater than the 90 th centile in the late third trimester is a significant risk factor for difficult birth. Prospective interventional trials should now be considered to evaluate the role of late gestation ultrasound assessment of FHC as a predictive tool toward selecting optimal mode of delivery.